Disputed Territories and International Criminal Law Israeli Settlements and the International Criminal Court. - McKenzie, Simon (London : Routledge, 2020)
It has been over 50 years since the beginning of the Israeli occupation of the Palestinian Territories. It is estimated that there are over 600,000 Israeli settlers living in the West Bank and East Jerusalem, and they are supported, protected, and maintained by the Israeli state. This book discusses whether international criminal law could apply to those responsible for allowing and promoting this growth, and examines what this application would reveal about the operation of international criminal law. It provides a comprehensive analysis of how the Rome Statute of the International Criminal Court could apply to the settlements in the West Bank through a close examination of the potential operation of two relevant Statute crimes: first, the war crime of transfer of population; and second, the war crime of unlawful appropriation of property. It also addresses the threshold question of whether the law of occupation applies to the West Bank, and how the principles of individual criminal responsibility might operate in this context. It explores the relevance and coherence of the legal arguments relied on by Israel in defence of the legality of the settlements and considers how these arguments might apply in the context of the Rome Statute. The work also has wider aims, raising questions about the Rome Statute's capacity to meet its aim of establishing a coherent and legally effective system of international criminal justice.
Description based upon print version of record.
OCLC-licensed vendor bibliographic record.
Keywords: International criminal law; LAW / General; LAW / Courts; LAW / Criminal Law / General